Structural Characteristics and Immunomodulatory Effects of a Long-Chain Polysaccharide From Laminaria japonica - Cui, Jiamei; Wang, Yunpeng; Kim, Eunyoung; Zhang, Chongyu; Zhang, Guiguo; Lee, Yunkyoung (Frontiers in Nutrition, 2022)
The polysaccharide derived from Laminaria japonica (LJPS) has been shown a variety of beneficial effects on improving human health, however the structural features and the bioactivities of a long-chain LJPS retain unclear. The aims of this study were to investigate the structural characteristics and its bioactivities of a novel long-chain LJPS. Results showed that the LJPS was composed of Fuc, Rha, Ara, Gal, Glc, Xyl, Man, Fru, Rib, GalA, GluA, GlcA, and ManA, with a molar ratio of 35.71: 1.48: 0.28: 13.16: 0.55: 2.97: 6.92: 0.58: 0.41: 0.14: 3.16: 15.84: 18.79. Thereof, Fuc, Gal, Man, GlcA, and ManA were the predominant components with the accumulated proportion of 93.6%. The LJPS consists of seven types monmers residues and mainly interchain glycosidic linkages were β-D-(1→2), α-D-(1→3), (1→4) and (1→6), and the molecular mass was 5.79×104 g/mol. Regarding the molecule conformation, LJPS was a multi-branched long-chain macromolecule and appeared in a denser crosslinking network with highly branched and helix domains in morphology. Additionally, the LJPS had no cell toxicity to mouse macrophage cells and exhibited the biphasic immuno-modulating capacity. The present findings suggested that the long-chain LJPS may be an attractive candidate as an immunopotentiating and anti-inflammatory functional food, and this study also provided a feasible approach for deciphering the structural characteristics and spatial conformation of plant-derived polysaccharides.